Assesment Perkembangan Bahasa Untuk Anak Tunagrahita - Khairiyah Rahmah Salsabila; Siti Nur Aisyah; Adinda Nazwa Kharisma; Fadhillah Dwi Indriani; Septy Nurfadhillah (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
Children with intellectual disabilities experience difficulties in intellectual functioning and adaptive behavior, which impact language development, both receptive and expressive. Language skills play a crucial role in supporting communication, social interaction, and children's learning success. Therefore, language development assessment is a crucial step in accurately identifying the abilities, obstacles, and learning needs of children with intellectual disabilities. This study aims to examine language development assessment in children with intellectual disabilities through a qualitative descriptive approach based on literature studies and empirical findings from special education practices. The results of the study indicate that systematic and ongoing language assessment can provide a comprehensive picture of children's language abilities, thus serving as a basis for developing individual learning programs and appropriate interventions. Therefore, language development assessment plays a strategic role in improving the quality of educational services for children with intellectual disabilities. Keywords: assessment, language development, children with intellectual disabilities, special education. Abstrak Anak tunagrahita mengalami hambatan dalam fungsi intelektual dan perilaku adaptif yang berdampak pada perkembangan bahasa, baik bahasa reseptif maupun ekspresif. Kemampuan bahasa memiliki peran penting dalam menunjang komunikasi, interaksi sosial, serta keberhasilan pembelajaran anak. Oleh karena itu, asesmen perkembangan bahasa menjadi langkah krusial untuk mengidentifikasi kemampuan, hambatan, dan kebutuhan belajar anak tunagrahita secara akurat. Penelitian ini bertujuan untuk mengkaji asesmen perkembangan bahasa pada anak tunagrahita melalui pendekatan deskriptif kualitatif berbasis studi literatur dan temuan empiris dari praktik pendidikan khusus. Hasil kajian menunjukkan bahwa asesmen bahasa yang dilakukan secara sistematis dan berkelanjutan dapat memberikan gambaran komprehensif mengenai kemampuan bahasa anak, sehingga dapat digunakan sebagai dasar penyusunan program pembelajaran individual dan intervensi yang sesuai. Dengan demikian, asesmen perkembangan bahasa memiliki peran strategis dalam meningkatkan kualitas layanan pendidikan bagi anak tunagrahita. Kata kunci: Asesmen, perkembangan bahasa, anak tunagrahita, pendidikan khusus